Normative Sports Law Analysis for Global Anti-Doping Justice - Wisnu Wisnu hadi; Muhammad Adrian Maulana; Sigit Nugroho; Muhammad Arief Setiawan; A. Ine Aprilia Damai; Aprillia Wulan Utari (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aims to analyze the development of anti-doping regulations from a sports law perspective and to assess the effectiveness of harmonization through the World Anti-Doping Code in ensuring procedural and substantive justice for athletes across jurisdictions. The study employs a normative legal approach with an analytical-critical orientation through an examination of the World Anti-Doping Code, the 2005 UNESCO Convention, and various national regulations that have adopted them. A conceptual approach is applied to examine the theories of polycentric regulation, legal legitimacy, and procedural justice, while a comparative approach is used to test the consistency of implementation across nations. The research findings indicate that the global anti-doping regime has evolved into a hybrid model integrating lex sportiva and international public law, resulting in formal harmonization of testing standards, evidentiary rules, and sanctions. However, significant implementation gaps exist, particularly regarding institutional capacity, access to legal aid, and the speed of dispute resolution, which impact the protection of athletes’ rights and the perceived legitimacy of the system. The study’s conclusions emphasize that normative harmonization does not yet fully align with substantive justice; therefore, strengthening national capacity and implementing policy reforms that are more responsive to social and political contexts are necessary to ensure equitable protection of athletes’ rights globally.